Removal of NO at low concentration from air in urban built environments by activated miscanthus biochar. (15th June 2023) - G. Díaz-Maroto, Carlos; Sáenz de Miera, Blanca; Collado, Laura; Fermoso, Jose; Mašek, Ondřej; Pizarro, Patricia; Serrano, David P.; Moreno, Inés; Fermoso, Javier
Abstract: This work presents an innovative and sustainable approach to remove NO emissions from urban ambient air in confined areas (underground parking areas or tunnels) using low-cost activated carbons obtained from Miscanthus biochar (MSP700) by physical activation (with CO2 or steam) at temperatures ranging from 800 to 900 °C. The NO removal capacity of the activated biochars was evaluated under different conditions (temperature, humidity and oxygen concentration) and compared against a commercial activated carbon. This last material showed a clear dependence on oxygen concentration and temperature, exhibiting a maximum capacity of 72.6% in air at 20 °C, whilst, its capacity notably decreased at higher temperatures, revealing that physical NO adsorption is the limiting step for the commercial sample that presents limited oxygen surface functionalities. In contrast, MSP700-activated biochars reached nearly complete NO removal (99.9%) at all tested temperatures in air ambient. Those MSP700-derived carbons only required low oxygen concentration (4 vol%) in the gas stream to achieve the full NO removal at 20 °C. Moreover, they also showed an excellent performance in the presence of H2 O, reaching NO removal higher than 96%. This remarkable activity results from the abundance of basic oxygenated surface groups, which act as active sites for NO/O2 adsorption, along with the presence of a homogeneous microporosity of 6 Å, which enables intimate contact between NO and O2 . These features promote the oxidation of NO to NO2, which is further retained over the carbon surface. Therefore, the activated biochars studied here could be considered promising materials for the efficient removal of NO at low concentrations from air at moderate temperatures, thus closely approaching real-life conditions in confined spaces. Graphical abstract: Image 1 Highlights: Full NO removal from air (5 ppm) by activated biochar at temperatures among 20-75 °C. Miscanthus derived carbons required only 4% O2 in the gas to reach full NO removal. Excellent NO removal of biochar-derived carbons in presence of H2 O (>96%). Basic oxygenated surface groups act as active sites for NO/O2 adsorption. The presence of microporosity of 6 Å enables intimate contact between NO and O2 .